2018
DOI: 10.1177/0266242618777792
|View full text |Cite
|
Sign up to set email alerts
|

Running faster and jumping higher? Survival and growth in international manufacturing new ventures

Abstract: Going international early is increasingly the choice of new ventures in manufacturing industries. However, does earliness provide a positive outcome for internationalisation? To answer this, we have longitudinally analysed 3181 manufacturing new ventures established between 2002 and 2012. Using Cox regressions, we found that the 124 late internationals had the lowest risk of failure, while the 229 early internationals could not compensate for their mortality risk with significantly higher levels of growth in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 75 publications
(113 reference statements)
1
51
0
1
Order By: Relevance
“…Taken together, the model developed and tested in our study adds to the knowledge about the drivers of internationalisation speed. We have identified key factors enabling firms to maintain a high internationalisation speed, a gap which has been identified in recent literature (Casillas and Acedo, 2013;Casillas and Moreno-Menéndez, 2014;Ibeh et al, 2018;Puig et al, 2018). In contributing to this discussion, we have shown that by carefully developing its knowledge acquisition strategy, the firm can accelerate its speed of capability development.…”
Section: Speed Of Capability Development and Speed Of Internationalismentioning
confidence: 85%
See 1 more Smart Citation
“…Taken together, the model developed and tested in our study adds to the knowledge about the drivers of internationalisation speed. We have identified key factors enabling firms to maintain a high internationalisation speed, a gap which has been identified in recent literature (Casillas and Acedo, 2013;Casillas and Moreno-Menéndez, 2014;Ibeh et al, 2018;Puig et al, 2018). In contributing to this discussion, we have shown that by carefully developing its knowledge acquisition strategy, the firm can accelerate its speed of capability development.…”
Section: Speed Of Capability Development and Speed Of Internationalismentioning
confidence: 85%
“…Fourth, we add knowledge about the drivers of internationalisation speed, which so far have attracted limited attention (Casillas and Acedo, 2013;Casillas and Moreno-Menéndez, 2014). Although, the factors enabling firms to maintain a high speed have not been explored in depth, (Ibeh et al, 2018;Puig et al, 2018), it has been argued that they are of both theoretical and practical importance (Prashantham et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…SMEs are increasingly integrated into the global economy and have gone further than what is often considered the first step of internationalization, that is, exporting and importing (Puig et al, 2018). For many firms, internationalization is a challenge from which the new models (i.e.…”
Section: Theoretical Background the Challenge Of Internationalization For An Smementioning
confidence: 99%
“…In fact, nowadays we can observe different realities characterized by an accelerated internationalization, a high commitment in foreign markets and a prompt global orientation. Within the last years, many SMEs have also accelerated their international commitment by investing in distant countries despite limited market knowledge, limited use of networks, and scarced international experience of the entrepreneurs and managers (Kalinic and Forza, 2012;Puig et al, 2018).…”
Section: Theoretical Background the Challenge Of Internationalization For An Smementioning
confidence: 99%
“…Additionally, ventures become international increasingly early, which requires firms to grow significantly quickly in short time period, a type of born to grow requirement, in order to survive and obtain the return needed to compensate the higher risk that such decision entails (Puig et al, 2018;Zucchella et al, 2007).…”
mentioning
confidence: 99%